Immunomodulatory and anticancer effects of moringa polyherbal infusions: potentials for preventive and therapeutic use - Talib, Wamidh H.; Al Junaidi, Hadeel Shaher; Alshaeri, Heba K.; Alasmari, Moudi M.; Hadi, Rawan W.; Alsayed, Ahmad Riyad; Law, Douglas (Frontiers in Immunology, 2025)
IntroductionPlant-based phytochemicals have shown potential as agents against cancer through various biological pathways, including immune system modulation. Combining natural compounds with synergistic interactions enhances the identification of molecular targets in cancer cells, demonstrating anticancer capabilities. The “miracle tree,” Moringa oleifera (Moringa), possesses remarkable nutritional and medicinal properties.AimThis study assesses the anti-tumor and immunomodulatory characteristics of M. oleifera aqueous leaf extract and its combinations with green tea, saffron, lavender, and turmeric.MethodsThe MTT assay evaluated the anti-proliferative effectiveness of uncombined M. oleifera and its combinations against three breast cancer cell lines. Quantitative LC-MS/MS spectrometry was performed on the most potent extracts. The Nitro Blue Tetrazolium Assay and Neutral Red Method were used to assess the effects of each extract on macrophage phagocytic and pinocytosis functions. Lymphocyte proliferation was also tested.ResultsThe anti-proliferative activity of Moringa-saffron showed the strongest anti-proliferative effect on T47-D and EMT6/P, with IC50 values of 1.14 ± 0.05 and 1.65 ± 0.27 mg/ml, respectively. The Moringa-green tea combination exhibited the highest anti-proliferative action against MDA-MB-231 among all combinations, with a 5.78 ± 0.06 mg/ml IC50 value. Moringa-lavender and Moringa-turmeric extracts showed minimal antiproliferation action. In contrast, uncombined Moringa had the lowest activity on the tested cell lines, with an IC50 greater than 6 mg/ml. For the immunomodulatory tests, Moringa-saffron and Moringa-green tea were the most effective combinations; they significantly induced macrophage phagocytosis, pinocytosis, and lymphocyte proliferation simultaneously. The LC-MS/MS analysis revealed the presence of flavonoids, phenols, coumarins, and alkaloids in the Moringa-saffron and Moringa-green tea combinations, which, along with their immune modulation activities, could contribute to their anticancer potential.ConclusionWhen combined with saffron or green tea, Moringa can effectively combat cancer and enhance immunomodulatory properties. Further studies are needed to understand the mechanism of action of these herbal infusions.